2015
DOI: 10.4012/dmj.2013-317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of myrrh on the strength of suture materials: an <i>in vitro</i> study

Abstract: The present in vitro study sought to determine the effects of myrrh-containing solutions on common suture materials used in periodontal surgery. Three commonly used suture materials (silk, polyglactin 910, polytetrafluoroethylene) were immersed in four thermostatically controlled experimental media to simulate daily oral rinsing activity, namely -artificial saliva, normal saline solution with 0.2% Commiphora myrrh, full-concentration (100%) Commiphora myrrh oil, and a myrrh-containing commercial mouthwash. Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
6
1
Order By: Relevance
“…Specimens failing at the reduced section and at the junction of the reduced and grip sections were discarded. Tensile strength was recorded by built‐in software integrated with the Instron machine …”
Section: Methodsmentioning
confidence: 99%
“…Specimens failing at the reduced section and at the junction of the reduced and grip sections were discarded. Tensile strength was recorded by built‐in software integrated with the Instron machine …”
Section: Methodsmentioning
confidence: 99%
“…The time frame and test frequencies of the present study were in accordance with the clinical relevance of the frequent oral and periodontal surgical procedures. Different studies have found a positive correlation between the reduction in tensile strength and resorption rates of distinct suture materials under controlled experimental conditions 26,27,28 . A prime element that can influence the resorption rate of suture materials is the variation in pH of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Within each type of suture (i.e., absorbable or non‐absorbable), there was marked variation regarding the type of suture material used (e.g., gut, polyglactin, nylon, polytetrafluoroethylene, silk). Given the reported differences among specific materials regarding loss of material properties in simulated oral environments 81 or induction of inflammatory tissue reaction, 12,82‐85 the use of a particular suture material might be of significance under certain circumstances.…”
Section: Discussionmentioning
confidence: 99%